(untitled) (CIPEEX, 2022)
IT IS UNDERSTOOD THAT PESTALOZZI INSTITUTE GUARANTEES THE QUALITY OF LIFE OF PEOPLE WITHSPECIAL NEEDS THROUGH THE ARTICULATION OF ACTIONS IN DEFENSE OF THEIR RIGHTS AND THE CONSTRUCTIONOF THEIR CITIZENSHIP. HOWEVER, SINCE IT IS A PHILANTHROPIC INSTITUTION, NOT ALL INSTITUTIONS HAVESUFFICIENT RESOURCES TO GUARANTEE THE QUALITY OF CARE FOR THEIR STUDENTS AND PATIENTS. JOHANNHEINRICH PESTALOZZI (1746-1827) WAS A GREAT SWISS EDUCATOR WHO DEDICATED HIS LIFE TO NEEDYCHILDREN AND THE APPRECIATION OF THE HUMAN BEING. CONSIDERED BY MANY THE GREATESTPHILOSOPHER OF MANKIND, HE INNOVATED THE PEDAGOGY OF HIS TIME, INFLUENCING SPECIAL EDUCATION.INFLUENCED BY PESTALOZZI’S WORK, THIAGO M. WURT, BORN IN GERMANY, CAME TO BRAZIL IN 1918 ANDFOUNDED THE FIRST SCHOOL IN THE COUNTRY, THE PESTALOZZI INSTITUTE, IN CANOAS, RIO GRANDE DO SUL.ALSO UNDER THE SAME INFLUENCE, HELENA ANTIPOFF, FOUNDED IN 1932, THE PESTALOZZI ASSOCIATION OFBELO HORIZONTE. SINCE THEN, EDUCATORS ENCHANTED WITH THE PESTALOZZI PHILOSOPHY, HAVE FOUNDEDIN ALL THE COUNTRY PESTALOZZI ASSOCIATIONS. THESE ENTITIES ARE AFFILIATED TO THE NATIONALFEDERATION OF PESTALOZZI ASSOCIATIONS - FENASP, WHOSE MISSION IS "TO GUARANTEE THE QUALITY OFLIFE OF PEOPLE WITH SPECIAL NEEDS THROUGH THE ARTICULATION OF ACTIONS IN DEFENSE OF THEIR RIGHTSAND THE CONSTRUCTION OF THEIR CITIZENSHIP". THE ASSOCIATION PESTALOZZI OF SENADOR CANEDO IS APHILANTHROPIC, NON-PROFIT INSTITUTION, WHOSE MISSION IS TO ACT IN DEFENSE OF THE RIGHTS OF DISABLEDAND NEEDY PEOPLE THROUGH JOINT ACTIONS WITH THE GOVERNMENT, COMPANIES AND SOCIETY, IN ORDERTO IMPROVE THEIR QUALITY OF LIFE, DEVELOPING THEIR POTENTIALITIES AND MAKING THEM USEFUL TOTHEMSELVES AND TO SOCIETY. IN THIS SENSE, THE PRESENT WORK HAS AS ITS GENERAL OBJECTIVE TOANALYZE WHETHER THE PESTALOZZI OF THE CITY OF SENADOR CANEDO HAS SUFFICIENT RESOURCES TOATTEND TO PEOPLE WITH DISABILITIES. A) TO IDENTIFY THE CLINICAL AND PEDAGOGICAL RESOURCES USED INTHE TREATMENT OF PEOPLE WITH DISABILITIES IN THE PESTALOZZI OF SENADOR CANEDO; B) TO DISCUSS THECONSTITUTIONAL PROVISION ON THE RIGHT TO EDUCATION AND TREATMENT OF DISABILITY. FOR THIS PURPOSE,THE PROBLEM WAS DEFINED AS FOLLOWS: DOES THE PESTALOZZI OF SENADOR CANEDO HAVE ENOUGHCLINICAL RESOURCES TO ATTEND PEOPLE WITH DISABILITIES? WE USED AS METHOD THE DESCRIPTIVE FIELDRESEARCH, THE QUANTITATIVE RESEARCH, THE BIBLIOGRAPHICAL RESEARCH AND THE EXPLANATORY RESEARCH.THE PRESENT ANALYSIS WILL BE IMPORTANT, AS IT AIMS TO ADDRESS THE LACK OF RESOURCES NEEDED ATTHE PESTALOZZI OF SENADOR CANEDO, CONSIDERING THAT THE INSTITUTION IS PHILANTHROPIC AND RELIESON SOCIETY’S CONTRIBUTION FOR IMPROVEMENT. THUS, IT IS IMPORTANT TO ADDRESS THE PROPOSED THEME,SINCE THE RESULTS OBTAINED POINT TO THE LACK OF PEDAGOGICAL AND CLINICAL RESOURCES AT PESTALOZZI.